Comparison of Efficay and Safety of First-Line Drugs (Imatinib Vs Nilotinib) in Newly Diagnosed pts of Ch Myeloid Leukemia - Ayesha Rahman, Sundus Durrani, Hajra Azhar, Nida Khalid, Najma Hafeez, Hafiz Muhammad Matloob (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tyrosine kinase inhibitors (TKI’s) revolutionized the treatment of chronic myeloid leukemia (CML). Aim: To compare the efficacy and safety between two Tyrosine Kinase Inhibitors among Pakistani population. Study Design: Randomized control trial. Methodology: Patients (n=124) were enrolled through simple random sampling. Prognostic scores were calculated for each patient. The institutional ethics committee of HFH approved this study protocol. Written informed consent was taken. Patients were randomly assigned to nilotinib 600 mg or imatinib 400 mg. The first analysis was done at 12 months of treatment. The second analysis was conducted after patients completed 24 months of therapy with TKIs. A consent form was signed by the participant before taking data. The basic end point was the rate of complete cytogenetic response (CCyR; 0% Ph+ metaphases by cytogenetics) at 12 months. Data was evaluated by using SPSS version 23. Chi-square test was applied with p-value of less than 0.05 was considered significant. Results: Nilotinib proved superior over imatinib in achieving complete cytogenetic response (94% vs 79%) with significant p-value. Both drugs showed similar risk profile to those from other international studies. Conclusion: It was concluded that Nilotinib proved clear benefit over imatinib in achieving higher rates of cytogenetic response in our study. The risk of events was comparable with imatinib and nilotinib; but each one showed different kinds of adverse events. Keywords: Chronic Myeloid Leukemia, Tyrosine Kinase Inhibitors and Cytogenetic Response.